KONSEP KEADILAN DALAM BAURAN PEMASARAN MENURUT PERSPEKTIF ISLAM - Rizal Ma'ruf Amidy Siregar (Institut Agama Islam Negeri Padngsidimpuan, 2016)
Business cannot be separated from trading/sales activities. Marketing mix (product, price, place and promotion) has been the main strategy of the majority of companies around the world in carrying out marketing activities. The capitalists marketing mix only prioritizing maximization of financial profit, while the marketing mix in the era of globalization is more focused on maximizing values. Islam offers the better of those two types of marketing. In conducting its product, pricing, place and promotion strategy, Islam prefers the interests of wider society. Islamic Marketing only looks the maximization of value if the aspects of fairness and honesty are met. It can be said if Islamic marketing forbids the slightest cheating in every process of the marketing mix.